The models of acquisition and teaching in a second language, and the hypothesis of the affective filter of Krashen - Al Shehri, Hamdan (Avances en Supervisión Educativa, 2012)
Theories of acquisition and learning in second language and Krashen’s affective filter hypothesis. There has been considerable research on some factors influencing academic performance of students based on emotional and behavioural disabilities/disorders (EBD) regarding academic achievement. Stephen Krashen tackles this problem from his theory of second language acquisition, called the monitor hypothesis, where he considers up to nine different hypotheses, among which, is the affective filter hypothesis. This academic paper proposes a study of this hypothesis considering the impediment to learning caused by negative emotional responses to one’s environment, in two different sections; approaches and methods in language teaching by one hand, and theories of acquisition and learning in second language by another, whereupon we suggest some activities, which seem to assuage these effects.